ЭКОЛОГИЯЛЫҚ ТƏРБИЯ - ЖОҚАРҒЫ РУЎХЫЙЛЫҚ ДЕРЕКЛЕРИНИҢ БИРИ - Муртазаева, З.Ғ. (FAN va JAMIYAT, 2020)
The article describes a wide range of aspects that form environmental education, human spirituality, mainly the education of the young generation through environmental ethics, the implementation of environmental culture. Exemplary efforts to instill a love for nature of the young generation, explanatory work in the family, exemplary teaching of our ancestors, measures taken in educational institutions, ways to encourage children to take care of nature are revealed.Along with the fulfillment of these tasks, it is analyzed that the young generation is hardworking, lives a peaceful and meaningful life in this world, and is closely linked with nature.